2016
DOI: 10.1016/j.cmi.2016.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Pros and cons of circumcision: an evidence-based overview

Abstract: Based on three large randomized controlled trials (RCTs) conducted in Africa, it can clearly be stated that circumcision lowers the risk of infection with the human immunodeficiency virus (HIV) and some sexually transmitted infections (STIs) among males in settings of high HIV and STI endemicity. Similar effects on STI risk may exist for females, although this may result from an indirect effect of decreasing risk of infection among male partners. It is unknown whether circumcision prevents HIV acquisition in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 86 publications
0
25
0
2
Order By: Relevance
“…Circumcision does not decrease the risk of HIV transmission from HIV-infected men to uninfected women [ 45 ]. The protective effect of partner circumcision in our study is likely an indirect effect related to lower HIV prevalence amongst circumcised partners who had unknown HIV status, as amongst males with known HIV status, uncircumcised males had considerably higher HIV prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Circumcision does not decrease the risk of HIV transmission from HIV-infected men to uninfected women [ 45 ]. The protective effect of partner circumcision in our study is likely an indirect effect related to lower HIV prevalence amongst circumcised partners who had unknown HIV status, as amongst males with known HIV status, uncircumcised males had considerably higher HIV prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to tackle HIV transmission by using strategies that may improve population health; and this includes male circumcision (MC). Three large randomized controlled trials (RCTs) conducted in African countries have shown that MC reduces the risk of acquiring HIV through heterosexual intercourse in males by 51–60% [ 1 ], and has been associated with a decreased risk of acquiring human papillomavirus, syphilis, and urinary tract infections [ 2 , 3 ]. These findings are currently being taken into account with regards to health recommendations and policy proposals.…”
Section: Introductionmentioning
confidence: 99%
“…Çalışmamızda da başvuru yaş ortalaması yaşlara göre 25,1 ay idi. Dünyada ve Türkiye'de sünnet işlemini cerrahlar yanında, yardımcı sağlık personelleri ve geleneksel sünnetçiler de yapmaktadırlar (4)(5)(6) . Eğitilmiş profesyoneller tarafından yapılan sünnetlerde komplikasyon oranı geleneksel sünnetçilere göre oldukça düşüktür (5,6) .…”
Section: Discussionunclassified